The Challenges of Vision Zero Implementation in Iran: A Qualitative Study - Safarpour, Hamid; Khorasani-Zavareh, Davoud; Soori, Hamid; Ghomian, Zohreh; Bagheri-Lankarani, Kamran; Mohammadi, Reza (Frontiers in Future Transportation, 2022)
Background: RTCs' multidimensional nature has piqued the interest of officials all around the world for many years. Vision Zero is one of the most innovative approaches to road safety. Vision Zero is a government initiative aimed at reducing RTC-related deaths and serious injuries. To effectively apply this approach in Iran, it is required to first identify the obstacles to execution. Therefore, the purpose of this study was to examine the obstacles to Vision Zero implementation in Iran. Methods: The qualitative content analysis method was used in this investigation. The participants were chosen using purposive, snowball, and maximum variety sampling methods. Data was collected through face-to-face interviews. Graneheim and Lundman's method was utilized to analyze data using the content analysis method. Results: There were 16 interviews with 14 participants in this study. The data was organized into four main categories and 13 subcategories to determine the obstacles to implementing Vision Zero. Managerial and administrative obstacles, as well as supportive, cultural and social, and transportation design and development challenges, were the main categories. Conclusion: In Iran, implementing Vision Zero necessitates the establishment of a lead agency that considers administrative and managerial, supportive and logistic, socio-cultural, transportation design and development, and infrastructure components. In addition, Vision Zero implementation and road safety improvement would require political commitment and support from the government and society. Vision Zero implementation and road safety management must take into account the ethics and value of human life.